The Role of Credit and Operational Risk on Banking Performance in State-Owned Banks: Empirical Insights from Indonesia - Ginna Novarianti Dwi Putri Pramesti; Agus Rohmat Hidayat (Sekolah Tinggi Agama Islam Kuningan, 2026)
Backround: Banking performance influenced by various factor risks, in particular risk credit and risk operational, which has implications significant for stability banking finance and the economy national research​. Objective: This aim analyze role risk credit and risk operational to performance of state-owned banks in Indonesia through review literature empirical and systematic from various studies national and international. Method: The methods used is systematic literature review (SLR), reviewing publication between 2012–2026 which discusses management risk, bank profitability, return on assets (ROA), and mitigation strategies risk in context state banking. Results: Analysis results show that risk high credit​ impact directly on bank profitability and quality portfolio loans, while risk operational, including weakness internal systems and processes, potentially lower efficiency and stability institutions. Effective mitigation strategies covers strengthening core capital, implementation standard management strict risk, as well as innovation digital technology for support credit monitoring and management operational. Conlusion: Research This conclude that management risk credit and operations in a way integrated important For guard performance of state-owned banks, increasing resilience financial, and support growth economy national.